Blended Learning and its Impact on 21st Century Student Learning: Blended Learning dan Dampaknya terhadap Pembelajaran Siswa Abad 21 - Hafiz, Muhammad; Agustini, Ketut; Suartama, I Kadek (Universitas Muhammadiyah Sidoarjo, 2025)
Learning in the digital age necessitates the development of critical thinking, collaboration, communication, and digital literacy. Blended learning, combining face-to-face and online instruction, offers a promising pedagogical model to address these evolving demands. Despite its growing application, there remains a lack of consolidated evidence evaluating its implementation across different educational levels and its contribution to 21st-century competencies. This study aims to systematically review recent literature on blended learning using the Systematic Literature Review (SLR) method following the PRISMA protocol. Data were sourced from Scopus, ScienceDirect, and Google Scholar, focusing on research from the past five years involving primary, secondary, and vocational education. The results show that blended learning positively impacts academic performance, student engagement, learning autonomy, and 21st-century skill development. However, gaps persist, particularly regarding infrastructure readiness and teacher proficiency. This study’s novelty lies in its contextualized analysis within the Indonesian education system, proposing blended learning as a strategic fit for the Merdeka Curriculum. The findings imply the need for robust policy support, teacher capacity-building, and investment in digital infrastructure to optimize blended learning’s effectiveness nationwide. Highlights: Enhances academic and 21st-century skills. Adapts to the Merdeka Curriculum context. Needs infrastructure and teacher readiness. Keywords: Blended Learning, Learning Models, Systematic Literature Review, 21st Century Skills, Innovative Education